The specifics of evidence in the tax process - Irina V. Glazunova (Правоприменение)
The subject of the article is peculiarities of evidence in the tax process.The main purpose of the article is to identify the existence or absence of specifics of evidence in the tax process.The description of the problem field. Each stage of the tax process is accompanied by tax authorities issuing tax legal acts; it requires them to obtain the necessary evidence. At the same time, theorists of tax procedural relations seek to circumvent the issue of the nature of tax procedural evidence. Some researchers believe that the theory of evidence, which formed the interdisciplinary institute of evidence, can eliminate the need for a theoretical definition of the tax evidence, but this is difficult to agree with, since tax evidence has specific features that determines the need of its independent research.The description of methodology. The author uses analysis, synthesis, comparison, interpretation of legal acts, economic approach as well as the dialectic and formal-legal methods.The main results and scope of their application. Evidence in the tax process is information about facts that are relevant to the adoption of a certain decision by the authorized subject of the tax process. Evidence must be obtained from acceptable and reliable sources and investigated in compliance with the procedure established by law.  It seems possible to set the list of evidence in the tax process legislation as follows: an oral explanation of the subject of the tax process or his representative; witness testimony; conclusion and testimony of an expert or specialist; written evidence, a protocol of a procedural action; material evidence; photo, video or audio materials. The evaluation of evidence by an authorized entity includes its consideration for relevance, admissibility, sufficiency and reliability. Only if the evidence meets the above criteria it will have probative value in a specific procedural situation.Conclusions. The purpose of the proof sets the maximum importance and its systemic significance for the entire tax process, since evidence-based knowledge traditionally appears to be the main supporting structure of the law enforcement process, in particular, evidence create the basis for its motives and conclusions. Accurate and objective establishment of factual circumstances of tax case is impossible without proper evidence. The main properties of evidence are relevance, admissibility, sufficiency and reliability.Keywords: evidence, tax process, tax procedural proof, tax authorities, means of proof, properties of evidence, individual tax legal acts, evidentiary information.